2008
DOI: 10.1002/hc.20391
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of optically active hydroxyphosphonates

Abstract: ABSTRACT:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…97 Kolodiazhnyi et al also demonstrated that racemic α-hydroxyphosphonates bearing dimenthyl auxiliary, prepared in the reaction of aldehydes with (−)-56 catalysed by DBU, could be used to obtain the corresponding α-ketophosphonates 92a-c (by oxidation with the use of pyridinium dichromate/trimethylchlorosilane) that were subsequently reduced in diastereoselective fashion to optically pure α-hydroxyphosphonates 89a,c,f (Scheme 31). 98,99 Similar strategy was also applied to β-ketophosphonate 93. The latter was prepared in a three-step one-pot procedure from dimenthyl methylphosphonate by the reaction with butyllithium to form the corresponding carbanion that was further reacted with cuprous bromide to form cuprous derivative that was finally reacted with acyl chlorides to produce the appropriate β-ketophosphonates.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…97 Kolodiazhnyi et al also demonstrated that racemic α-hydroxyphosphonates bearing dimenthyl auxiliary, prepared in the reaction of aldehydes with (−)-56 catalysed by DBU, could be used to obtain the corresponding α-ketophosphonates 92a-c (by oxidation with the use of pyridinium dichromate/trimethylchlorosilane) that were subsequently reduced in diastereoselective fashion to optically pure α-hydroxyphosphonates 89a,c,f (Scheme 31). 98,99 Similar strategy was also applied to β-ketophosphonate 93. The latter was prepared in a three-step one-pot procedure from dimenthyl methylphosphonate by the reaction with butyllithium to form the corresponding carbanion that was further reacted with cuprous bromide to form cuprous derivative that was finally reacted with acyl chlorides to produce the appropriate β-ketophosphonates.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…The reaction proceeded rather slowly, but with good yields of chiral hydroxyphosphonates. To complete the reaction, it took from 1 to 3 days at +20 • C. The structure of the products was studied by X-ray diffraction analysis [32]. The stereoselectivity of the reaction depended on the structure of the initial reagents and reaction conditions.…”
Section: Diastereoselective Substitution Reactionsmentioning
confidence: 99%
“…In particular, the chiral reducing agent NaBH 4 -Pro, derived from NaBH 4 and (S)-proline, reduced ketophosphonates with good enantioselectivity. This reducing agent has been applied to the synthesis of a number of hydroxyphosphonates (Figure 13) [32,33]. reducing agent has been applied to the synthesis of a number of hydroxyphosphonates (Figure 13) [32,33].…”
Section: Diastereoselective Substitution Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other variations, pyridinium dichromate [ 105 ] or pyridinium chlorochromate [ 106 ] were applied successfully to give α-ketophosphonates 35 . The reaction under discussion was also reported using KMnO 4 as the oxidant ( Scheme 18 ).…”
Section: Reactions Of α-Hydroxyphosphonatesmentioning
confidence: 99%